Reducing Allostatic Load in Depression and Anxiety Disorders: Physical Activity and Yoga Practice as Add-On Therapies - D'Alessio, Luciana; Korman, Guido Pablo; Sarudiansky, Mercedes; Guelman, Laura Ruth; Scévola, Laura; Pastore, Alejandra; Obregón, Amilcar; Roldán, Emilio J. A. (Frontiers in Psychiatry, 2020)
The allostatic load (AL) index constitutes a useful tool to objectively assess the biological aspects of chronic stress in clinical practice. AL index has been positively correlated with cumulative chronic stress (physical and psychosocial stressors) and with a high risk to develop pathological conditions (e.g., metabolic syndrome, cardiovascular pathology, inflammatory disorders) and the so-called stress-related psychiatric disorders, including anxiety and depressive disorders. Chronic stress has negative effects on brain neuroplasticity, especially on hippocampal neurogenesis and these effects may be reversed by antidepressant treatments. Several evidences indicate that non-pharmacological interventions based on physical activity and yoga practice may add synergizing benefits to classical treatments (antidepressant and benzodiazepines) for depression and anxiety, reducing the negative effects of chronic stress. The aim of this review is to provide a general overview of current knowledge on AL and chronic stress in relation to depression and anxiety, physical activity and yoga practice.